Schisandrin B Attenuates Diabetic Cardiomyopathy by Targeting MyD88 and Inhibiting MyD88‐Dependent Inflammation. Issue 31 (30th September 2022) - Luo, Wu; Lin, Ke; Hua, Junyi; Han, Jibo; Zhang, Qiuyan; Chen, Lingfeng; Khan, Zia A.; Wu, Gaojun; Wang, Yi; Liang, Guang
Abstract: Diabetes manifests as chronic inflammation and leads to the development diabetic cardiomyopathy (DCM). Targeting key proteins in inflammatory signaling may provide new therapy for DCM. In this study, the authors explore the pharmacological effects and mechanisms of Schisandrin B (Sch B), a natural compound with anti‐inflammatory activity against DCM. It is shown that Sch B prevents high‐level glucose (HG)‐induced hypertrophic and fibrotic responses in cultured cardiomyocytes. RNA sequencing and inflammatory qPCR microarray show that Sch B mainly affects myeloid differentiation primary response 88 (MyD88)‐dependent inflammatory gene expression in HG‐challenged cardiomyocytes. Further studies indicate that Sch B directly binds to and inhibits MyD88 activation, but does not alter MyD88‐independent Toll‐like receptor signaling in vivo and in vitro. Inhibiting or silencing MyD88 is associated with reduced levels of HG‐induced inflammatory cytokines and myocardial injuries in vitro. Treatment of type 1 and type 2 diabetic mice with Sch B protects heart function, reduces myocardial injuries, and decreases secretion of inflammatory cytokines. Cardiomyocyte‐specific MyD88 knockout also protects mice against cardiac inflammation and injury in type 1 diabetic mice. In conclusion, these studies show that cardiomyocyte MyD88 plays an apathogenetic role in DCM and Sch B specifically targets MyD88 to reduce inflammatory DCM. Abstract : Hyperglycemia/high‐concentration glucose (HG) activates Toll‐like receptors (TLRs)‐MyD88 in cardiomyocytes and heart tissues. MyD88‐mediated activation of TAK1‐MAPKs/NF‐ κ B signaling causes increased production of inflammatory factors, leading to cardiomyocyte hypertrophy and fibrosis. Schisandrin B is able to bind to the TIR domain of MyD88, potentially through Thr‐272 and Arg‐288 sites. Such binding suppresses TAK1‐MAPKs/NF‐ κ B activation and attenuates inflammatory diabetic cardiomyopathy.